A MODEL FOR PERSONNEL ACCESS CONTROL TO INFORMATION RESOURCES OF INDUSTRIAL ENTERPRISES BASED ON RBAC AND BLOCKCHAIN TECHNOLOGY - YAMNYCH, ANDRII; KOROBEINIKOVA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article investigates the integration of Role-Based Access Control (RBAC) with blockchain technology to enhance access control and information security within an enterprise. The proposed model uses smart contracts written in the Solidity environment to manage role assignments, access rights, and event logging. The integration includes features such as role delegation, revocation, and normalization of the role hierarchy, ensuring a dynamic and adaptable access control structure. The RBAC model defines user roles, permissions, and access constraints, ensuring that each user’s access level aligns with their designated responsibilities within the enterprise. The smart contract was divided into three main parts. The first part established the RBAC initialization and role assignment (where user roles were mapped to addresses), and access rights were defined. Functions like assignRole and setAccessRight allowed administrators to assign roles to users and configure access rights. The second part handled access management and event logging (specific functions like initiateAccess and confirmAccess regulated access to enterprise resources based on predefined roles). These functions checked whether the user’s role met the necessary criteria before granting or confirming access, and all actions were logged through events (AccessInitiated and AccessConfirmed). The third part extended the functionality by introducing delegation, revocation, and normalization. The delegateRole function allowed the temporary transfer of role permissions between users (important for scenarios where a user could not fulfill their duties). The revokeRole function ensured the immediate revocation of roles when they were no longer valid, while maintaining the integrity of the access control system. The normalizeRoles function regulated the establishment of hierarchical relationships between roles, optimizing role management and reducing the storage space required for access policies. The application of the proposed model within a blockchain-based environment significantly enhances the security and transparency of access control policies. The immutable nature of blockchain technology prevents unauthorized changes to access control records and ensures that all access-related actions are traceable and verifiable.